Solid electrolyte membrane and preparation method and application thereof

The solid electrolyte membrane with a sulfide solid electrolyte and binder enhances the air stability and chemical stability, reduces hydrogen sulfide gas generation, and forms a dielectric layer to inhibit lithium dendrite formation, improving lithium-ion battery stability and performance.

CN119253041APending Publication Date: 2025-01-03ENVISION AESC JAPAN LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411545099.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Current sulfide solid electrolytes in lithium ion batteries suffer from poor chemical stability, air instability, generation of toxic hydrogen sulfide gas, environmental hazards, complex production conditions, and high interfacial impedance, affecting battery performance and safety.

Method used

A solid electrolyte membrane comprising a sulfide solid electrolyte with a molecular formula Li f P 1-g E g S w O g Q z, where E is selected from Mg, Ca, Sr, Ba, Zn, Cr, or Pb, and Q is Cl or Br, with a binder, enhancing air stability and forming a dielectric layer at the electrolyte/lithium metal interface to inhibit lithium dendrite formation and improve ionic conductivity.

Benefits of technology

The solution significantly improves the stability and performance of lithium-ion batteries by reducing toxic gas generation, enhancing chemical stability, and promoting lithium ion diffusion, thereby improving battery life and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253041A_ABST
    Figure CN119253041A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte membrane and a preparation method and application thereof. The solid electrolyte membrane comprises a binder; the molecular formula of the sulfide solid electrolyte is Li < f > P < 1-g > Eg < S < w > O < g > Q < z >; wherein, 5lt; flt; 10; 0 lt; glt; 1, 3lt; wlt; 6, 4lt; w + glt; 6, 0lt; zlt, zlt; 2; e is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb; q is selected from one or more of Cl, Br or I; the ionic conductivity of the solid electrolyte membrane is 1 * 10 <-3 > S / cm to 2 * 10 <-2 > S / cm. According to the solid-state electrolyte membrane and the preparation method and application thereof, the stability of the conductivity of the solid-state electrolyte membrane can be improved, the air stability is enhanced, the service life of an all-solid-state lithium ion battery is prolonged, and the safety of the all-solid-state lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and particularly to a solid electrolyte membrane, a preparation method thereof and an application thereof. Background Art

[0002] With the rapid development of new energy technologies, lithium ion batteries are widely used due to their advantages such as high energy density and long cycle life. However, traditional lithium ion batteries use liquid electrolytes, which have safety hazards such as electrolyte leakage and combustion. To overcome these disadvantages, solid electrolyte materials have received extensive attention. Among them, sulfide solid electrolytes are favored due to their high ionic conductivity and good mechanical properties. Currently, a variety of sulfide solid electrolyte materials have been developed, such as Li 10 GeP2S 12 or Li6PS5Cl, etc.

[0003] However, most current sulfide electrolytes have poor chemical stability, are easily decomposed in air, generate toxic hydrogen sulfide gas, pose hazards to the environment and human health, and have strict production conditions, increasing production complexity and costs. In addition, the interfacial compatibility between sulfide solid electrolytes and electrode materials also needs to be improved, and the interfacial impedance is large, affecting battery performance. Summary of the Invention

[0004] The present invention provides a solid electrolyte membrane, a preparation method thereof and an application thereof. By using the solid electrolyte membrane, preparation method and application provided by the present invention, the stability of the ionic conductivity of the solid electrolyte membrane can be improved, the air stability can be enhanced, the interfacial properties between the electrolyte / active material can be improved, and the life and safety of all-solid-state lithium ion batteries can be improved.

[0005] To solve the above technical problems, the present invention provides a solid electrolyte membrane, which at least includes:

[0006] A binder; and

[0007] A sulfide solid electrolyte, the molecular formula of the sulfide solid electrolyte being Li f P 1-g E g S w O g Q z ; wherein, 5 < f < 10; 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2; E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb; Q is selected from one or more of Cl, Br or I;

[0008] The ionic conductivity of the solid electrolyte membrane is 1×10 -3 S / cm~2×10-2 S / cm.

[0009] In one embodiment of the present invention, E is Mg.

[0010] In one embodiment of the present invention, Q is selected from Cl; the value range of g is 0.01≤g≤0.1.

[0011] In one embodiment of the present invention, the thickness of the solid electrolyte membrane is 1 μm to 200 μm.

[0012] In one embodiment of the present invention, the mass ratio of the binder to the sulfide solid electrolyte is 0.1:99.9 to 10:90.

[0013] The present invention also provides a method for preparing the solid electrolyte membrane, characterized in that it comprises the steps of:

[0014] According to the chemical formula of the sulfide solid electrolyte, the raw materials are mixed evenly according to the stoichiometric amount, and then placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder;

[0015] calcining the sulfide solid electrolyte precursor powder at a preset temperature to obtain the sulfide solid electrolyte; and

[0016] The sulfide solid electrolyte is mixed with a binder, and the solid electrolyte membrane is obtained by dry preparation or wet preparation.

[0017] In one embodiment of the present invention, the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S; the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5; the E source is selected from one or more of oxides of E or sulfides of E; the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, MgS, CaS, SrS, BaS, ZnS, CrS, SnS or PbS; the Q source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2; the O element in the chemical formula comes from the oxide of E.

[0018] In one embodiment of the present invention, when the solid electrolyte membrane is prepared by a dry method, the binder is selected from a first binder, and the first binder is selected from one or more of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

[0019] In one embodiment of the present invention, when the solid electrolyte membrane is prepared by a wet method, the binder is selected from a second binder, and the second binder is selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid, polyurethane, polyvinyl alcohol, sodium alginate, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-cyclodextrin polymer, polypropylene emulsion, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

[0020] The present invention also provides an all-solid-state lithium-ion battery, comprising at least:

[0021] A positive electrode sheet, wherein the positive electrode sheet comprises a halide solid electrolyte, wherein the halide solid electrolyte comprises Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 ;

[0022] A negative electrode; and

[0023] A solid electrolyte membrane is provided between the adjacent positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane is selected from the solid electrolyte membranes described above.

[0024] The present invention also provides an electronic device, comprising the all-solid-state lithium-ion battery described above.

[0025] In summary, the present invention proposes a solid electrolyte membrane and a preparation method and application thereof. By introducing E element, O element and Q element into the sulfide solid electrolyte in the solid electrolyte membrane, the air stability of the solid electrolyte membrane is effectively improved, the H2S gas generated by atmospheric degradation is reduced, and the air stability and chemical stability of the solid electrolyte membrane are enhanced. A special dielectric layer can be formed at the electrolyte / lithium metal negative electrode interface, which can ensure the ionic conductivity of the solid electrolyte membrane, promote the rapid movement of lithium ions and the uniform distribution of the electric field. It can help control the nucleation and growth of lithium, prevent the formation of lithium dendrites, significantly improve the stability and performance of lithium-ion batteries, improve the life and safety of all-solid-state lithium-ion batteries, and improve the compatibility of solid electrolyte membranes with active materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0027] Figure 1 Schematic diagram of the process of preparing a solid electrolyte membrane by dry method in one embodiment of the present invention.

[0028] Figure 2 This is a 1C / 1C long cycle performance diagram of the all-solid-state lithium-ion battery in Example 3 at room temperature. DETAILED DESCRIPTION

[0029] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0030] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0031] The technical solution of the present invention is further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The present invention provides a solid electrolyte membrane, which includes a binder and a sulfide solid electrolyte, wherein the molecular formula of the sulfide solid electrolyte is Li f P 1-g E g S w O g Q zAmong them, 5 < f < 10; 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from one or more of Cl, Br or I. Among them, introducing E element and O element into the sulfide solid electrolyte rich in halogen elements will form P-O and E-S bonds in the crystal structure, effectively improving the air stability of the sulfide solid electrolyte, reducing the H2S gas generated by atmospheric degradation, and enhancing the air stability and chemical stability of the sulfide solid electrolyte. In addition, when using this sulfide solid electrolyte to assemble a all-solid-state lithium-ion battery, a special dielectric layer can be formed at the electrolyte / lithium metal negative electrode interface. This dielectric layer contains components such as LiCl, Li2O and Li-Mg alloy. Among them, Li2O has good ionic conductivity, while Li-Mg alloy promotes the rapid movement of lithium ions and the uniform distribution of the electric field. The high interfacial energy of LiCl helps to control the nucleation and growth of lithium, preventing the formation of lithium dendrites. These characteristics combined effectively promote the diffusion of lithium ions between the electrodes and inhibit the growth of lithium dendrites. Therefore, the sulfide solid electrolyte provided by this application can significantly improve the stability and performance of the lithium-ion battery, and improve the life and safety of the all-solid-state lithium-ion battery and the lithium battery.

[0033] In an embodiment of the present invention, E is for example selected from Mg. Doping Mg can trigger the electron aggregation around the S atom, inhibit the electron acceptance of Li, and at the same time the generated self-limiting interface hinders the redox reaction between the sulfide electrolyte and Li metal. That is, by doping Mg, the electron distribution in the sulfide solid electrolyte can be adjusted, the electron acceptance of Li can be inhibited, thereby reducing the parasitic redox reaction between the electrolyte and metallic lithium, improving the cycle stability and performance of the battery, and improving the practicality and reliability of the sulfide electrolyte.

[0034] In an embodiment of the present invention, Q is selected as a halogen element, and according to the different halogens, the degree of anion disorder between the 4a and 4c sites in the crystal structure of the sulfide solid electrolyte is different, from a small number of anti-site defects with Q being I to 60% site disorder with Q being Cl, and the lithium ionic conductivity of these compounds mainly depends on the degree of disorder of the anion and cation site occupancy. Therefore, Q is for example selected as Cl to improve the ionic conductivity and electrochemical stability of the sulfide solid electrolyte and improve the voltage stability. The value range of g is 0.01 ≤ g ≤ 0.1. When the doping amount is too low, an effective dielectric layer may not be formed. Excessive doping will cause excessive lattice distortion and damage the original crystal structure, which may lead to a decrease in the structural stability of the material, and even phase separation or amorphization, thereby reducing the ionic conductivity of the material. In a specific embodiment of the present invention, g is optimally 0.02 to improve the cycle performance of the lithium-ion battery.

[0035] In one embodiment of the present invention, the thickness of the solid electrolyte membrane is, for example, 1 μm to 200 μm, and the ionic conductivity is, for example, 1×10 -3 S / cm~2×10 -2 S / cm, and the ionic conductivity is relatively stable at low temperatures, and the solid electrolyte membrane can be prepared in batches in a dry room with a low dew point, which greatly simplifies the preparation process and reduces the preparation cost. The solid electrolyte membrane provided by the present application can be well matched with the lithium metal negative electrode, and a high-energy density and high-performance all-solid-state lithium battery can be prepared.

[0036] In one embodiment of the present invention, the mass ratio of the binder to the sulfide solid electrolyte is 0.1:99.9 to 10:90, and the binder is selected from one of the first binder and the second binder. Among them, the first binder is selected from one or more of polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer, etc. The second binder is selected from PVDF, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinylpyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer, etc., or one or more thereof. By adding a binder, the processability of the solid electrolyte membrane can be improved, the volume expansion can be alleviated, the structure of the solid electrolyte membrane can be stabilized, and a self-supporting solid electrolyte membrane can be obtained.

[0037] The present invention also proposes a method for preparing a solid electrolyte membrane, which is used to prepare the above-mentioned solid electrolyte membrane, and at least includes: according to the chemical formula of the sulfide solid electrolyte, the raw materials are mixed evenly according to the stoichiometric ratio, and then placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder; the sulfide solid electrolyte precursor powder is calcined at a preset temperature to obtain a sulfide solid electrolyte; the sulfide solid electrolyte is mixed with a binder, and a solid electrolyte membrane is obtained by dry preparation or wet preparation.

[0038] In one embodiment of the present invention, according to the chemical formula of the sulfide solid electrolyte Li f P 1-g E g S w O g Q z , the Li source, P source, E source, S source and Q source are uniformly mixed according to stoichiometric ratio, wherein the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S, the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5, the E source is selected from one or more of oxides of E or sulfides of E, the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, MgS, CaS, SrS, BaS, ZnS, CrS, SnS or PbS, the Q source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, and the O element in the chemical formula comes from the oxide of E. After the raw materials are evenly mixed, they are placed in a ball mill and ball milled in an inert gas atmosphere, wherein the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50 rpm to 1500 rpm, and the ball milling time is, for example, 1 h to 48 h, to obtain a sulfide solid electrolyte precursor powder.

[0039] In one embodiment of the present invention, the sulfide solid electrolyte precursor powder is calcined at a preset temperature, wherein the preset temperature is 400° C. to 600° C., and the calcination time is 1 h to 18 h, to obtain a sulfide solid electrolyte.

[0040] See also Figure 1As shown, in one embodiment of the present invention, when the solid electrolyte membrane is prepared by a dry method, for example, a powder extrusion molding method is used, and the binder is selected from the first binder. Specifically, after the sulfide solid electrolyte and the first binder are mixed evenly by low-temperature shearing, they are quickly heated up for high-temperature shearing mixing to obtain a mixed material, and the mixed material is added to a roller press for high-temperature rolling to obtain a solid electrolyte membrane. Among them, the mass ratio of the first binder to the sulfide solid electrolyte is, for example, 0.1:99.9~5:95, the temperature of low-temperature shearing is, for example, -30℃~15℃, the temperature of high-temperature shearing is, for example, 20℃~200℃, and the temperature of high-temperature rolling is, for example, 20℃~200℃. In the dry preparation process, the first binder is wrapped around the sulfide solid electrolyte in a network shape, which can improve the mechanical strength and chemical stability of the solid electrolyte membrane, and can maintain stable contact between the electrolyte and the electrode material during the battery charging and discharging process, thereby improving the performance and life of the battery.

[0041] In one embodiment of the present invention, when the solid electrolyte membrane is prepared by a wet method, for example, a wet coating method and an electrostatic spraying method, the binder is selected from the second binder. Specifically, the sulfide solid electrolyte, the second binder and the solvent are mixed evenly to obtain an electrolyte slurry, and then the electrolyte slurry is coated on the substrate by a wet coating or electrostatic spraying method, and then the substrate coated with the electrolyte slurry is dried and peeled off to obtain a solid electrolyte membrane. Among them, the solvent is, for example, selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethanedithiol, acetonitrile, tetrahydrofuran, methanol, isopropyl ether, acetone, hexene, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone. In the electrolyte slurry, the content of the sulfide solid electrolyte is, for example, 30wt% to 90wt%, the content of the second binder is, for example, 0.1wt% to 10wt%, the content of the solvent is, for example, 10wt% to 50wt%, and after drying, the mass ratio of the second binder to the sulfide solid electrolyte is, for example, 0.1:30 to 10:90. The substrate is, for example, selected from polyethylene glycol terephthalate (PET) film, smooth aluminum foil or release paper, etc., for easy demoulding, and the drying temperature is, for example, 30°C to 250°C.

[0042] The present invention also provides an all-solid-state lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the solid electrolyte membrane is arranged between adjacent positive electrode sheets and negative electrode sheets. The solid electrolyte membrane is selected from the above-mentioned solid electrolyte membranes to improve the performance of the all-solid-state lithium-ion battery.

[0043] In one embodiment of the present invention, the positive electrode plate includes a positive electrode active material and a halide solid electrolyte, and the positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA). The halide solid electrolyte includes Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , the halide solid electrolyte does not produce heat reaction with the de-lithiation positive electrode active material, thereby improving the safety of the lithium-ion battery. The positive electrode sheet also includes a conductive agent and a binder, wherein the conductive agent is, for example, one or a combination of at least two of conductive carbon black (Super P, SP), carbon nanotubes (Carbon Nano-tube, CNT), vapor-grown carbon fiber (VaporGrown Carbon Fiber, VGCF) or graphene. The binder is, for example, polytetrafluoroethylene (PTFE) and its derivatives.

[0044] In one embodiment of the present invention, the mass ratio of the positive electrode active material, the halide solid electrolyte, the conductive agent and the binder is, for example, (65-78): (20-30): (1-3): (1-2). In this embodiment, the mass ratio of the positive electrode active material, the halide solid electrolyte, the conductive agent and the binder is, for example, 69: 29: 1: 1. Among them, the conductive agent is a combination of conductive carbon black (super-P) and vapor-grown carbon fiber (VGCF), and the mass ratio of conductive carbon black to vapor-grown carbon fiber is 1: 1, and the binder is, for example, polytetrafluoroethylene. After the positive electrode active material, the halide solid electrolyte, the conductive agent and the binder are uniformly mixed, a mixed powder is obtained, and the positive electrode sheet is obtained by dry pressing.

[0045] In one embodiment of the present invention, the negative electrode plate is, for example, one or more of a metal lithium plate, a metal indium plate, or a lithium indium alloy plate, and the negative electrode plate includes, for example, a negative electrode active material, and the negative electrode active material is selected from one or more of a graphite material, a silicon material, or a composite material of a graphite material and a silicon material. In one embodiment of the present invention, when the negative electrode plate includes a negative electrode active material, the negative electrode plate also includes a solid electrolyte, a conductive agent, and a binder, wherein the solid electrolyte is, for example, a halide solid electrolyte or a sulfide electrolyte, and the present application does not make specific restrictions. The binder is, for example, at least one of polyisoprene, polyethylene, or polypropylene, and the conductive agent is, for example, at least one of carbon nanotubes, carbon fibers, or acetylene black, and the present application does not limit the ratio of the negative electrode active material, the solid electrolyte, the conductive agent, and the binder, and the selection is made according to the manufacturing requirements, and the negative electrode plate is, for example, obtained by dry pressing.

[0046] In one embodiment of the present invention, the negative electrode sheet is, for example, a metal lithium sheet, and the positive electrode sheet, the solid electrolyte membrane, and the negative electrode sheet are sequentially stacked, packaged, hot pressed, and cold pressed, and then wrapped with an aluminum plastic film or the like under vacuum or an inert atmosphere to obtain an all-solid-state soft-package lithium-ion battery. The assembly process of the all-solid-state lithium-ion battery is, for example, completed in a glove box with an argon atmosphere.

[0047] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0048] Example 1

[0049] Preparation of sulfide solid electrolyte: 2.03 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.02 mol of MgO were milled by high-energy ball milling, with a ball-to-material ratio of 30:1 and a rotation speed of 500 rpm. The precursor powder was sintered at 500 °C for 10 h and cooled to obtain Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5 Sulfide solid electrolyte.

[0050] Preparation of solid electrolyte membrane: electrolyte Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5The mixture is mixed with PTFE at a mass ratio of 99:1 at -20°C, and the temperature is raised to 80°C to make the PTFE fiberized to obtain a mixed material. The mixed material is extruded into a roller press, and the solid electrolyte membrane is rolled to a thickness of 5 μm at 80°C by adjusting the gap of the roller press.

[0051] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The PTFE is prepared by mixing in a mass ratio of 69:1:29:1 and dry-processing to form the positive electrode sheet, and the conductive agent is super-P and VGCF in a mass ratio of 1:1.

[0052] Negative electrode sheet: The negative electrode sheet is made of metal lithium sheet.

[0053] Assembly of all-solid-state batteries: The positive electrode sheets, solid electrolyte membranes and negative electrode sheets prepared above are stacked, packaged, hot-pressed and cold-pressed to form all-solid-state soft-pack batteries.

[0054] Assembly of symmetrical battery: Place the counter electrode Li on both sides of the solid electrolyte membrane and assemble it with the solid electrolyte membrane into a Li / Li symmetrical battery.

[0055] Example 2

[0056] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 10 μm, and other operations were consistent with Example 1.

[0057] Example 3

[0058] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 30 μm, and other operations were consistent with Example 1.

[0059] Example 4

[0060] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 50 μm, and other operations were consistent with Example 1.

[0061] Example 5

[0062] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 100 μm, and other operations were consistent with Example 1.

[0063] Example 6

[0064] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 200 μm, and other operations were consistent with Example 1.

[0065] Example 7

[0066] The chemical formula of the sulfide solid electrolyte prepared by 2.015 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.01 mol MgO is Li 5.53 P 0.99 Mg 0.01 S 4.49 O 0.01 Cl 1.5 , other operations remain the same as those in Example 3.

[0067] Example 8

[0068] The chemical formula of the sulfide solid electrolyte prepared by 2.0225 mol Li2S, 1.5 mol LiCl, 0.4925 mol P2S5 and 0.015 mol MgO is Li 5.545 P 0.985 Mg 0.015 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 3.

[0069] Example 9

[0070] The chemical formula of the sulfide solid electrolyte prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.48 mol P2S5 and 0.04 mol MgO is Li 5.62 P 0.96 Mg 0.04 S 4.46 O 0.04 Cl 1.5 , other operations remain the same as those in Example 3.

[0071] Example 10

[0072] The chemical formula of the sulfide solid electrolyte prepared by 2.09 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.06 mol MgO is Li 5.68 P 0.94 Mg 0.06 S 4.44 O 0.06 Cl 1.5 , other operations remain the same as those in Example 3.

[0073] Embodiment 11

[0074] The chemical formula of the sulfide solid electrolyte prepared by 2.12 mol Li2S, 1.5 mol LiCl, 0.46 mol P2S5 and 0.08 mol MgO is Li 5.74 P 0.92 Mg 0.08 S 4.42 O 0.02 Cl 1.5 , other operations remain the same as those in Example 3.

[0075] Example 12

[0076] The chemical formula of the sulfide solid electrolyte prepared by 2.15 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.1 mol MgO is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 , other operations remain the same as those in Example 3.

[0077] Example 13

[0078] The chemical formula of the sulfide solid electrolyte prepared by 1.83 mol Li2S, 1.9 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.16 P 0.98 Mg 0.02 S 4.08 O 0.02 Cl 1.9 . , other operations are consistent with those in Example 3.

[0079] Embodiment 14

[0080] The chemical formula of the sulfide solid electrolyte prepared by 2.53 mol Li2S, 1 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 6.06 P 0.98 Mg 0.02 S 4.98 O 0.02 C1, other operations are consistent with those in Example 3.

[0081] Embodiment 15

[0082] The chemical formula of the sulfide solid electrolyte prepared by 3.03 mol Li2S, 0.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 6.56 P 0.98 Mg0.02 S 5.48 O 0.02 Cl 0.5 , other operations remain the same as those in Example 3.

[0083] Example 16

[0084] The chemical formula of the sulfide solid electrolyte prepared by 3.43 mol Li2S, 0.1 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 6.96 P 0.98 Mg 0.02 S 5.88 O 0.02 Cl 0.1 , other operations remain the same as those in Example 3.

[0085] Embodiment 17

[0086] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.4 mol LiCl, 0.1 mol LiBr, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.4 Br 0.1 , other operations remain the same as those in Example 3.

[0087] Embodiment 18

[0088] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.3 Br 0.1 I0 .1 , other operations remain the same as those in Example 3.

[0089] Embodiment 19

[0090] ETFE was selected as the adhesive, and other operations were consistent with those in Example 3.

[0091] Embodiment 20

[0092] PCTFE was selected as the binder, and other operations were consistent with those in Example 3.

[0093] Embodiment 21

[0094] Preparation of sulfide solid electrolyte: 2.03 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.02 mol of MgO are milled by high-energy ball milling to obtain precursor powder, where the ball-to-material ratio is 30:1 and the rotation speed is 500 rpm. The precursor powder is sintered at 500 ° C for 10 hours and Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5 Sulfide solid electrolyte.

[0095] Preparation of solid electrolyte membrane: Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5 , SBR binder and xylene solvent were evenly mixed in a mass ratio of 49:1:50 to form an electrolyte slurry, and the electrolyte slurry was scraped onto a smooth aluminum foil using a coater, and then vacuum dried and peeled off at 80°C to form a 30μm thick solid electrolyte membrane.

[0096] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The PTFE is prepared by mixing in a mass ratio of 69:1:29:1 and dry-processing to form the positive electrode sheet, and the conductive agent is super-P and VGCF in a mass ratio of 1:1.

[0097] Negative electrode sheet: The negative electrode sheet is made of metal lithium sheet.

[0098] Assembly of all-solid-state batteries: The positive electrode sheets, solid electrolyte membranes and negative electrode sheets prepared above are stacked, packaged, hot-pressed and cold-pressed to form all-solid-state soft-pack batteries.

[0099] Assembly of symmetrical battery: Place the counter electrode Li on both sides of the solid electrolyte membrane and assemble it with the solid electrolyte membrane into a Li / Li symmetrical battery.

[0100] Embodiment 22

[0101] PVDF was selected as the binder, and other operations were consistent with Example 21.

[0102] Embodiment 23

[0103] PAA was selected as the binder, and other operations were consistent with Example 21.

[0104] Embodiment 24

[0105] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol CaO is Li 5.56 P 0.98 Ca 0.02 S 4.48 O 0.02 Cl 1.5 , other operations remain the same as those in Example 3.

[0106] Embodiment 25

[0107] The chemical formula of the sulfide solid electrolyte prepared by 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol ZnO is Li 5.56 P 0.98 Zn 0.02 S 4.48 O 0.02 Cl 1.5 , other operations remain the same as those in Example 3.

[0108] Comparative Example 1

[0109] The chemical formula of the solution prepared by 2 mol of Li2S, 1.5 mol of LiCl, and 0.5 mol of P2S5 is Li 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 3.

[0110] Comparative Example 2

[0111] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.4 mol of LiCl, 0.1 mol of LiBr and 0.5 mol of P2S5 is Li 5.5 PS 4.5 Cl 1.4 Br 0.1 , other operations remain the same as those in Example 3.

[0112] Comparative Example 3

[0113] The chemical formula of the electrolyte prepared by 2 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI and 0.5 mol of P2S5 is Li5.5 PS 4.5 Cl 1.3 Br 0.1 I 0.1 , other operations remain the same as those in Example 3.

[0114] Comparative Example 4

[0115] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 1 μm, and other operations were consistent with Example 3.

[0116] In Examples 1-25 and Comparative Examples 1-4 of the present invention, different solid electrolyte membranes are used to test the ionic conductivity of the solid electrolyte membranes, and the solid electrolyte membranes are exposed to a dry room at -40°C for 24 hours, and then the ionic conductivity test is performed again. In this embodiment, the ionic conductivity is obtained, for example, by an AC impedance method, and the test results are shown in Table 1.

[0117] In Examples 1-25 and Comparative Examples 1-4 of the present invention, different sulfide solid electrolytes are used to obtain lithium-ion batteries. The lithium-ion batteries prepared above are subjected to long-cycle charge and discharge at 25°C, and their discharge capacity is measured, and the energy density is calculated. The working voltage range of the battery test is 2.5V to 4.3V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded as the 1C discharge capacity. When the battery capacity reaches 80% of the first cycle capacity (80% State of Health, 80% SOH), the test is terminated to obtain the number of cycles at room temperature. The symmetrical battery is charged at 1 mA / cm 2 The constant current charge-discharge cycle test was carried out at a current density of , and the test results are shown in Table 2.

[0118] Table 1. Ionic conductivity of sulfide solid electrolytes in Examples 1-25 and Comparative Examples 1-4

[0119]

[0120] Table 2. Test results of lithium-ion batteries and symmetrical batteries in Examples 1-25 and Comparative Examples 1-4

[0121]

[0122] Please refer to Table 1 and Table 2. Comparison of Examples 1-6 and Comparative Example 4 shows that as the thickness of the solid electrolyte membrane increases, the retention rate of the ionic conductivity of the solid electrolyte membrane at low temperatures increases, and the cycle performance of the lithium-ion battery first gradually increases and then gradually decreases. And when the solid electrolyte membrane is too thin, a battery short circuit occurs when the number of cycles is low. Therefore, in combination with the retention rate of ionic conductivity and cycle performance, there is an optimal range for the thickness of the solid electrolyte membrane.

[0123] Please refer to Table 1 and Table 2. Comparative Examples 3, 7-12 show that when the E element in the sulfide solid electrolyte selects Mg, as the doping amount of Mg increases, the cycle performance of the lithium-ion battery gradually increases and then gradually decreases. And as the doping amount of the E element increases, the ionic conductivity of the solid electrolyte membrane decreases, but the ionic conductivity retention rate after exposure to -40°C dry room for 24h increases, enhancing the air stability and chemical stability of the solid electrolyte membrane, and improving the stability and performance of the battery. It shows that an appropriate amount of E element doping can help form a stable solid electrolyte interface (Solid Electrolyte Interface, SEI) and reduce the side reactions between the solid electrolyte and the electrode material. When the doping amount is too low, an effective SEI film may not be formed. Excessive doping can cause excessive lattice distortion and destroy the original crystal structure, which may cause the structural stability of the material to decrease, and even phase separation or amorphization may occur, thereby reducing the ionic conductivity of the material. Therefore, controlling the doping amount of E in the sulfide solid electrolyte can improve the cycle life and safety of the all-solid-state lithium-ion battery, while maintaining the ionic conductivity at a high level, ensuring the rate performance of the lithium-ion battery, and improving the charge and discharge efficiency and cycle life.

[0124] See also Figure 2 As shown, in the all-solid-state lithium-ion battery of Example 3, during the cycle at room temperature, the current density used for constant current charging and discharging is 1C, Figure 2 It can be seen that at a current density of 1C, the all-solid-state lithium-ion battery in Example 3 still has an energy storage capacity of about 140 mAh / g after 500 cycles, indicating that the sulfide solid electrolyte has excellent reaction kinetics and cycle stability, and the obtained solid electrolyte membrane has a good gain effect on the cycle stability and reaction activity specific capacity of the battery. The all-solid-state lithium-ion battery has excellent specific capacity, rate performance and cycle life.

[0125] As shown in Table 1 and Table 2, by comparing Examples 3 and 13-16, it can be seen that when the Mg element doping amount is the same, increasing or decreasing the Cl element content will cause a serious decrease in ionic conductivity, and will reduce the cycle performance of the lithium ion battery. Therefore, the Cl element content is controlled to ensure the ionic conductivity of the sulfide solid electrolyte and the performance of the lithium ion battery.

[0126] Please refer to Table 1 and Table 2. By comparing Examples 3 and 17-18, it can be seen that when the doping amount of Mg element is the same, the addition of one or more of Br or I elements will reduce the cycle performance of the battery. This is because the added Br or I may introduce additional lattice defects, which may become obstacles to lithium ion transmission and further reduce the ionic conductivity of the electrolyte. Therefore, Q selects Cl element, which can improve the ionic conductivity and electrochemical stability of the sulfide solid electrolyte and improve the voltage stability.

[0127] Please refer to Table 1 and Table 2. It can be seen from the comparison of Examples 3, 17-18 and Comparative Examples 1-3 that when the E element and the O element are not added to the sulfide solid electrolyte, the lithium-ion battery has almost no cycle performance and a short circuit occurs quickly, indicating that when the E element and the O element are missing, the chemical stability of the sulfide solid electrolyte material is poor, the mechanical strength is insufficient, and it is difficult to ensure the long-term cycle performance of the lithium-ion battery. By introducing the E element and the O element, the cycle performance of the lithium-ion battery can be improved. It can be seen from Comparative Examples 3, 24-25 that when the E doping element selects other elements, it can also increase the ionic conductivity retention rate, improve the stability of the sulfide solid electrolyte, and improve the cycle performance of the lithium-ion battery, but it is weaker than Mg doping. Therefore, when Mg is doped, the performance of the lithium-ion battery is best.

[0128] Please refer to Table 1 and Table 2. Comparative Examples 3 and 19-20 show that in the dry preparation process, when different first binders are selected, the ionic conductivity of the solid electrolyte membrane and the performance of the lithium-ion battery will also be affected. When the first binder is selected from PTFE, the ionic conductivity of the solid electrolyte membrane and the performance of the lithium-ion battery are optimal. Comparative Examples 21-23 show that in the wet preparation process, when different second binders are selected, the ionic conductivity of the solid electrolyte membrane and the performance of the lithium-ion battery will also be affected. When the second binder is selected from PAA, the ionic conductivity of the solid electrolyte membrane and the performance of the lithium-ion battery are optimal. Comparative Examples 3 and 21 show that the solid electrolyte membrane prepared by the dry process is better than the solid electrolyte membrane prepared by the wet process. This is because a large amount of organic solvents are used in the wet process, and the organic solvents react slightly with the electrolyte, thereby reducing the performance of the electrolyte membrane, while the dry process does not introduce solvents.

[0129] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.

[0130] In summary, the present invention proposes a solid electrolyte membrane and a preparation method and application thereof. By introducing E element, O element and Q element into the sulfide solid electrolyte in the solid electrolyte membrane, the air stability of the solid electrolyte membrane is effectively improved, the H2S gas generated by atmospheric degradation is reduced, and the air stability and chemical stability of the solid electrolyte membrane are enhanced. A special dielectric layer can be formed at the electrolyte / lithium metal negative electrode interface, which can ensure the ionic conductivity of the solid electrolyte membrane, promote the rapid movement of lithium ions and the uniform distribution of the electric field. It can help control the nucleation and growth of lithium, prevent the formation of lithium dendrites, significantly improve the stability and performance of lithium-ion batteries, improve the life and safety of all-solid-state lithium-ion batteries, and improve the compatibility of solid electrolyte membranes with active materials.

[0131] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0132] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A solid electrolyte membrane, characterized in that: At least: Binder; and Sulfide solid electrolyte, the molecular formula of the sulfide solid electrolyte is Li f P 1-g E g S w O g Q z ; wherein, 5 < f < 10; 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2; E is selected from one or more of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb; Q is selected from one or more of Cl, Br or I; The ionic conductivity of the solid electrolyte membrane is 1×10 -3 S / cm~2×10 -2 S / cm.

2. The solid electrolyte membrane according to claim 1, characterized in that E is Mg.

3. The solid electrolyte membrane according to claim 1, characterized in that Q is selected from Cl; the value range of g is 0.01≤g≤0.

1.

4. The solid electrolyte membrane according to claim 1, characterized in that: The solid electrolyte membrane has a thickness of 1 μm to 200 μm.

5. The solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the binder to the sulfide solid electrolyte is 0.1:99.9 to 10:

90.

6. A method for preparing a solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: Includes steps: According to the chemical formula of the sulfide solid electrolyte, the raw materials are mixed evenly according to the stoichiometric amount, and then placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder; calcining the sulfide solid electrolyte precursor powder at a preset temperature to obtain the sulfide solid electrolyte; as well as The sulfide solid electrolyte is mixed with a binder, and the solid electrolyte membrane is obtained by dry preparation or wet preparation.

7. The method for preparing a solid electrolyte membrane according to claim 6, characterized in that: The Li source is selected from one or more of LiCl, LiBr, LiI or Li2S; the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5; the E source is selected from one or more of E oxides or E sulfides; the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, MgS, CaS, SrS, BaS, ZnS, CrS, SnS or PbS; the Q source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2; the O element in the chemical formula comes from the oxide of E.

8. The method for preparing a solid electrolyte membrane according to claim 6, characterized in that: When the solid electrolyte membrane is prepared by a dry method, the binder is selected from a first binder, and the first binder is selected from one or more of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

9. The method for preparing a solid electrolyte membrane according to claim 6, characterized in that: When the solid electrolyte membrane is prepared by a wet method, the binder is selected from a second binder, and the second binder is selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid, polyurethane, polyvinyl alcohol, sodium alginate, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-cyclodextrin polymer, polypropylene emulsion, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

10. An all-solid-state lithium-ion battery, characterized in that: At least: A positive electrode sheet, wherein the positive electrode sheet comprises a halide solid electrolyte, wherein the halide solid electrolyte comprises Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 ; A negative electrode; and A solid electrolyte membrane, wherein the solid electrolyte membrane is disposed between the adjacent positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane is selected from the solid electrolyte membrane according to any one of claims 1 to 5.

11. An electronic device, characterized in that: Including the all-solid-state lithium-ion battery as described in claim 10.

Citation Information

Cited By

  • Sulfide-based composite electrolyte with high air stability as well as preparation method and application of sulfide-based composite electrolyte

    CN122224917A